Struktur Komunitas Burung Pada Tiga Tipe Habitat di Kampus Universitas Andalas, Padang - Andira, Ayu; Nurdin, Jabang; Novarino, Wilson (Jurnal Biologi UNAND, 2015)
A study on the structure ofbird communities in three types of habitatsat Andalas University, Padang, has been carried out from November 2012 to February 2013. This study aimed to determine the structure of bird communities in those habitats. We used mist-net to catch understory birds. We succesfully caught 72 individuals which belong to24 species, 20 genera, 12 families and 3 orders, including four species of migratory birds. The highest abundance was found in the secondary forest, and the lowest was in herbaceous dominated vegetation. The diversity indiceswere generally moderate (H’= 1,897 – 2,466) Keywords: bird community, habitat type, mist-netting